Análisis y diseño del esquema de seguridad de la red de datos del Hospital Isidro Ayora de la ciudad de Loja e implementación de la seguridad lógica utilizando software libre. - Díaz Chávez, Andrea Elizabeth (2012)
Today's communications networks are increasingly important to organizations as they are the means by which information is transmitted and should not compromise the integrity, availability and confidentiality of the same. Security in information and computing systems has become one of the biggest problems from the globalization of the Internet. The objective of security is to ensure privacy of information and continuity of service, trying to minimize the vulnerability of systems or information contained in them, and trying to protect private networks and resources while maintaining the benefits of connecting to a public network and private network. This project involves a detailed study on network security data Isidro Ayora Hospital in the city of Loja, for which it has been used in the analysis phase methodologies such as OSSTMM (Open Methodology Manual Safety Testing ), to search for vulnerabilities the GNU / Linux Backtrack, OCTAVE (Operationally Critical Assets and Vulnerability Evaluation Threats) to analysis and risk management, in the design phase for the determination of requirements and design security scheme network methodology Cisco SAFE (Security Model for Enterprise Networks) that also involves the definition of security policies for both the end user and the Information Management Unit Isidro Ayora Hospital and in the implementation phase using free software tools for network security data.